MULTIGROUP MODELING BASED PATH ANALYSIS ON PANEL DATA IN THE STUDY OF PRODUCTION PERFORMANCE IN SMALL AND MEDIUM INDUSTRIES IN MALANG - Hapsari, Meilina Retno; Sa'diyah, Nur Kamilah (VARIANCE: Journal of Statistics and Its Applications, 2025)
This study aims to determine the effect of the number of workers on production performance through the amount of production between small and medium industries in Malang City. This study applies multigroup modeling based on path analysis on panel data on variables that affect industrial production performance in Malang and the application of the Hypothesis of Linear Parameter Function in the multigroup model, which is the second group. This data source is secondary data from Malang Industrial data. The sample in this study is all data from small and medium industries in Malang City over several years. The results showed that the Hypothesis of Linear Parameter Function can be applied to the two-group model, that is, in a medium industry, where three significant paths are obtained. In the small industry, there are two considerable paths. Based on the coefficient of total determination, the data diversity can explain the model of 96.0%. At the same time, the remaining 4.0% is affected by other variables. The small and medium industry model shows that the number of workers significantly affects production. The effect is greater in medium industries, which is 0.935, compared to small industries, which is 0.737.